Edaphic macrofauna in the establishment of an agroforestry system in the High Andean region of Southern Colombia - Muñoz-Rodriguez, Martin Alonso; Santacruz-Ortiz, Ana Carolina (Revista de Ciencias Agrícolas, 2024)
Biological degradation of the soil due to inadequate agricultural practices that eliminate vegetative cover and, therefore, organic matter, reduces the biological communities that perform important ecological functions in the soil. The objective of the study was to evaluate some biological properties of the soil in an agroforestry system with Morella pubescens intercropped with Smallanthus sonchifolius and in a degraded pasture of Cenchrus clandestinum. The trial was conducted at the Botana Experimental Farm, Nariño, at 2,820 meters above sea level. Density, richness and Simpson and Shannon-Wiener diversity indices were determined. A Randomized Complete Block Design with three replications was used. The treatments corresponded to sowing distances of S. sonchifolius. T1: sown at 1x1m, T2: 0.8x0.8m, T3: 0.5x0.5m and the control T4 corresponded to degraded pasture of C. clandestinum. The tree component M. pubescens was established at 4x4m between seedlings and 9m between rows. Soil macrofauna sampling was carried out following the monolithic TSBF method, collecting at depths of (0-10, 10-20 and 20-30cm). A total density of 6,496i/m2 individuals was found. The highest value was obtained in T3 (3,168i/m2) represented by the taxonomic groups Diptera and Haplotaxida. Higher values of richness were observed in T1. The Shannon index was higher in T2 (0.66) while T1 (0.80) presented higher dominance in morphospecies. Density and richness were higher in the agroforestry arrangement than in the degraded Cenchrus clandestinum pasture. Treatments, depth and their interaction did not significantly affect morphospecies diversity.